LE DOUBLE REPENTIR D'AUSTIN. ENQUÊTE SUR LE MODE DE TRAITEMENT DU LANGAGE PAR LATOUR. - Foot, Robin (Symposium: Canadian Journal of Continental Philosophy / Revue Canadienne de Philosophie Continentale)
The theory of language adopted by Latour turns away from "linguistic turn" and comes down to a "descriptive" conception of language. This article seeks to question this hypothesis from a survey of its relationship to language. The lack of reference to the theory of speech acts constitutes a starting point to the issue.